OPTIMIZING STUDENTS’ LOW FREQUENCY WORDS ACHIEVEMENT THROUGH IMPLEMENTING MODIFIED KEYWORD METHOD - Anjar Muttaqin (LET: Linguistics, Literature and English Teaching Journal)
There has been a great deal of research discussing the most effective ways to memorize vocabulary in order to support the skills of students especially reading. This research was conducted to optimize the achievement of low-frequency words through Modified Keyword Method (MKM). The subject of this research was the second semester of grade XI of multimedia 2 students of academic year 2015/2016. The subject of research consisted of 34 students. The researcher chose this class as the research’ subject for most of the students find it difficult to comprehend English text well due to their vocabulary inadequacy especially on low-frequency words. The research method used is class action research. The researcher conducts planning, implementation, observation and reflection during the research. This method was planned one cycle which consists of three meetings. There are 21 low-frequency words to grasp in order to be able to understand two texts of English. Data was collected through questionnaire and vocabulary test. The findings of the research show that the entire students (100%) achieved the criteria of success. 28 students who were classified into average class surpassed the targeted level with 72.28 as the mean score. 4 students passed the criteria of success (50) while the other 24 students passed the target of high class students (75). Meanwhile, the rest of the 6 students who belonged to the high class classification succeeded to achieve the criteria of success (minimum passing grade/ Kriteria ketuntasan minimal=75) with the mean score of 98. The achievement is also strengthened by the positive result of the questionnaire. In short, Modified Keyword Method as a teaching strategy proved to be successful in improving students’ vocabulary of low frequency words.